1990
DOI: 10.1111/j.1600-0536.1990.tb00075.x
|View full text |Cite
|
Sign up to set email alerts
|

Ranking of surfactant skin irritancy in vivo in man using the plastic occlusion stress test (POST)

Abstract: Irritant effects and disturbance of water-holding capacity induced by surfactants were investigated using the plastic occlusion stress test (POST) technique. 4 surfactants (sodium lauryl sulphate (SLS), sorbitan monolaurate, cocoamidopropyl betaine and benzalkonium chloride) and an amphoteric/nonionic (A/N) mix were investigated. 1 x daily for 3 days, test surfactants were applied to marked sites (open) on the volar forearm. After 24 h occlusion with a plastic chamber on the 4th day, skin surface water loss (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 13 publications
0
31
0
2
Order By: Relevance
“…A fim de melhorar a precisão das medições da PTEA, outras abordagens dinâmicas têm sido sugeridas. Os testes de acumulação de humidade (MAT) [9] , de sorção/dessorção [10] e de oclusão plástica (POST) [11] são exemplos relevantes que servem como base conceptual para o modelo aqui aplicado, permitindo uma descrição quantitativa mais precisa do balanço de massa de água cutânea ao longo do tempo [12][13][14] . O presente estudo avalia o impacto da utilização de um gel desinfetante de base alcoólica sobre a função de 'barreira' epidérmica, usando uma abordagem de modelação cinética das curvas de dessorção da PTEA após um POST.…”
Section: Methodsunclassified
See 1 more Smart Citation
“…A fim de melhorar a precisão das medições da PTEA, outras abordagens dinâmicas têm sido sugeridas. Os testes de acumulação de humidade (MAT) [9] , de sorção/dessorção [10] e de oclusão plástica (POST) [11] são exemplos relevantes que servem como base conceptual para o modelo aqui aplicado, permitindo uma descrição quantitativa mais precisa do balanço de massa de água cutânea ao longo do tempo [12][13][14] . O presente estudo avalia o impacto da utilização de um gel desinfetante de base alcoólica sobre a função de 'barreira' epidérmica, usando uma abordagem de modelação cinética das curvas de dessorção da PTEA após um POST.…”
Section: Methodsunclassified
“…In order to improve the precision of TEWL measurements, other dynamical approaches have been suggested. The moisture accumulation test (MAT) [9] , the sorption/desorption test [10] , and the plastic occlusion stress test (POST) [11] are relevant examples serving as the conceptual basis for the compartmental model here applied, allowing a more accurate quantitative description of the cutaneous water mass balance over time [12][13][14] . This study evaluates the impact of the use of an alcoholbased gel sanitizer on the epidermal 'barrier' function, using a kinetic approach of TEWL desorption curves following a POST test.…”
Section: Introductionmentioning
confidence: 99%
“…SDS is also known to cause skin dermatitis (Berardesca et al, 1990) and oral mucosal irritation (Rantanen et al, 2002). The concentration of SDS in dentifrices usually ranges from 0.5% to 2.0% (Barkvoll et al, 1989), and it has been demonstrated that contacting of the dentifrice containing 1.5% SDS provokes desquamation of the oral mucosa in human (Herlofson and Barkvoll, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Portanto, uma pele saudável tende a possuir valores de PTEA mais baixos e, portanto, uma grande quantidade de água no estrato córneo [7] . A sensibilidade desta variável é maior quando se usam testes de provocação, incluindo o teste de oclusão plástica (POST) comumente usado [8][9][10] . Este estudo tem como objetivo avaliar o impacto do uso regular de quatro semanas de duração de um gel desinfetante à base de álcool na hidratação cutânea e na função epidérmica 'barreira' in vivo, usando um modelo cinético já estabelecido de curvas de dessorção de PTEA na sequência de um teste POST.…”
Section: Introductionunclassified
“…Healthy skin tends to possess lower TEWL values and therefore, a larger amount of water in the stratum corneum [7] . The sensitivity of this variable is increased when employing provocation tests, including the commonly used plastic occlusion stress test (POST) [8][9][10] . This study aims to evaluate the impact of a four week-long regular use of an alcohol-based gel hand sanitizer on in vivo skin hydration and the epidermal 'barrier' function, using a previously established kinetic modelling of TEWL desorption curves following a POST test.…”
Section: Introductionmentioning
confidence: 99%